البعث في القرآن الكريم ــــسورة ياسين أنموذجا - منصور, صواالح; زلاسي, سمية (جامعة الوادي university of eloued, 2017)
تدف هذه الرسالة إىل تقدمي دراسة فكرة عن إثبات البعث يف سورة ياسني ، ويتم ذلك من خالل دراسة تفسريية لبعض اآليات القرآنية هلذه السورة . وعلى هذا النحو فقد تضمن حبثنا فصلني كاملني حبيث متثل كل منهما على إطارين اإلطار النظري ، واألخر اإلطار التطبيقي ، فأما الفصل األول[اإلطار النظري]فقد تنولنا مفاهيم أولية وتعريفات ملصطلحات البحث وأيضا بيان فضائل السورة ، وأسباب نزوهلا ، وأهدافها الرئيسية،وإبراز ، وأما الفصل الثاين التناسب بني آياهتا[اإلطار التطبيقي]فقد تضمن اآليات اليت تتكلم عن البعث واالستشهاد عليها بأقوال املفسرين القدامى واملعاصرين . Research Summary : The purpose of this thesis is to presenting a study of the idea that emphasizes the resurrection of Sura which named "Yassin". it is done through an interpretive study of some Quranic verses of this sura. In this way, our research include two whole chapters, each of which is based on theoretical framework , and applied framework. In The first chapter ( theoretical framework) we talk about the primary concepts and definitions of the terms' research , as well as we give the main reasons and excellences of this sura. Also, show the concordance between its verses. While in the second {Applied Framework} which includes the verses that speak about resurrection. It gives the martyrdom that was saying by the old and modern interpreters
مقارنة